Re-visioning the "Eye in the Sky": targeted drone strikes and an ethics of the encounter. Issue 1 (2nd January 2020) - Robson, Matthew
ABSTRACT: The complexities which beset any attempts to ascribe a foundational ethic to matters of a political stripe are well known, and continue to provoke fierce debate within studies of international relations, geopolitics and security studies. Unsurprisingly, these questions have taken on crucial import within the sub-field of critical terrorism studies (CTS), as authors grapple with the range of counter-terrorism, counter-radicalisation and counter-extremism practices enacted by the Western state as part of an ongoing 'War on Terror.' And while much of this scholarship has been invaluable in problematizing the concept of 'terrorism' per se, normative questions have proven somewhat more elusive. Through a reading of the film Eye in the Sky, along with its take on the controversial counter-terrorism practice of targeted drone assassinations, this article reiterates the case for an ethical approach which takes radical difference as the basis for any engagement with the Other. Moreover, and following international relations authors of a poststructuralist lineage, it will be argued that supplementing Levinasian ethics with Derridean deconstruction can open up new and useful ways of approaching such seemingly intractable ethical conundrums.